T27. COGNITIVE RESERVE IN CHILD AND ADOLESCENT OFFSPRING OF PATIENTS DIANOSED WITH SCHIZOPHRENIA OR BIPOLAR DISORDER. (18th May 2020) - De la Serna, Elena; Camprodon-Boadas, Patricia; Sugranyes, Gisela; Torrent, Carla; Sole, Brisa; Montejo, Laura; Ilzarbe, Daniel; Baeza, Inmaculada; Romero, Soledad; Castro-Fornieles, Josefina
Abstract: Background: Cognitive Reserve (CR) is defined as the ability of the brain to cope and deal with physiological or pathological brain injuries. In the field of psychiatry, higher levels of CR have been associated with lower levels of psychotic symptoms, higher psycho-social functioning and higher cognitive performance, suggesting that CR should be considered as a protective factor (Barnett et al., 2006; Amoretti et al., 2016). This study aims to compare CR levels in a sample of adolescents and young adult offspring of patients with schizophrenia or bipolar disorder who are at high risk of developing these disorders (HR) and compared them with a group of healthy controls (HC). We also assess the utility of CR in predicting clinical and cognitive variables. Methods: Participants were 85 HR and 45 HC. A CR proxy was calculated based on premorbid IQ, socio-occupational attainment and social activities. Clinical assessment included: the Structured Interview for Prodromal Symptoms (SOPS), the Young Mania Rating Scale (YMRS) and the Hamilton Depression Rating Scale (HDRS). Neuropsychological assessment included: Working Memory, Processing Speed, Verbal Memory, attention and executive functioning. A factorial analysis was conducted in order to obtain a single CR measure. Differences between groups in CR were assessed via MANCOVA and linear regressions were conducted to check the effectiveness of CR in predicting clinical and neuropsychological variables. Results: No significant differences were observed in age or gender between HR and HC groups. Socioeconomic status was lower in HR subjects (F=8.100, p=0.005).CR was significantly lower in the HR group than in the HC group (F=17.522; p<0.001). Moreover, the CR proxy was able to correctly classify 72.7% of the sample as either HR or HC. Our proxy was able to predict the following clinical variables in the HR group: negative (F=9.269; p=0.002), and total (F=7.290; p=0.009) prodromal symptoms, the YMRS (F=11.597; P<0.001) and the HDRS (F=12.761; p<0.001). In terms of neuropsychological variables, RC predicted WM (F=9.738; p=0.003), PS (F=4.557; p=0.037) and verbal memory [immediate (F=6.999; p=0.010) and delayed recall (F=10.990; P=0.002)] in the HR sample. Discussion: HR subjects have lower CR than controls. CR is associated with clinical and neuropsychological variables. To our knowledge no previous studies have assessed CR in high risk samples. Nevertheless, studies conducted in adult first episode psychotic samples have shown an association between CR and the severity of symptoms.